Fibrinolysis and the biliary tree. Issue 1 (January 1997) - Scott-Coombes, D M; Whawell, S A; Havranek, E G; Thompson, J N
Abstract : AIMS: To investigate the fibrinolytic activity of normal and calculous human bile. METHODS: Fibrinolytic properties of the biliary tract were studied in patients with gall bladder stones (n = 7) compared with acalculous gall bladders (n = 8). RESULTS: Bile plasminogen activating activity was detected in a wide range in both groups (calculous bile median 0.35 IU/ml; range: 0.06-6.59, versus normal bile 0.70 IU/ml; 0.19-3.56). There was no difference in the bile concentration of tissue plasminogen activator between the two groups (calculous bile median 21.5 ng/ml versus normal bile 9.5 ng/ml), which was present in much greater concentrations than urokinase (calculous bile median 0.10 ng/ml versus normal bile 0.36 ng/ml). Both plasminogen activators were detected in low concentrations in gall bladder mucosa. Plasminogen activator inhibitors-1 and 2 were detected in bile in significantly greater concentrations in patients with gall bladder stones (plasminogen activator inhibitor-1: calculous bile median 15 ng/ml versus normal bile < 2 ng/ml, plasminogen activator inhibitor-2: 157 ng/ml versus < 6 ng/ml, p < 0.05). CONCLUSIONS: Human bile possesses fibrinolytic activity and the principal plasminogen activator in bile seems to be tissue plasminogen activator. Plasminogen activator inhibitors were present in greater concentrations in stone bile and may be a factor in the pathogenesis of gall stone formation.